Psychological Well-Being among University Students in Malaysia. - Lukman@Zawawi, Mohamad; Azlini, Chik; Normala, Riza (2018)
Unexceptionally for university students, the occurrences of psychological distress are believed to be higher for them to encounter. There has been an increaseamong theinternationalpublic concerning the mental health and the impact of unidentified and untreated mental illness among university students.Theaim of this study is to identify the level of psychological well-being of Universiti Sultan Zainal Abidin (UniSZA) students.Depression, Anxiety and Stress Scale (DASS- 21) were used for data collection together with the sociodemographic questionnaire. Data were collected from 443 UniSZA students. This study used descriptive analysis to obtain accurate results. The findings of this study showed that depression, anxiety, and stress found among UniSZA students were 42.2%, 73.7%, and 34.8% respectively. Findings revealed that students who faced psychological distress level possessed relatively hightendency for depression, stress, and anxiety.Psychological distress poses negative impacts on the physical, mental and academic. What is more worrying is that students who faced this kind of problem do not seek help or treatment because of the public stigma against mental illness.